Sony Pictures Entertainment, Inc. : a cybersecurity attack from North Korea (B) - Alexander, Meredith; Chase, Ashley; Chase, Kelly; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On November 24, 2014, Sony Pictures Entertainment, a subsidiary of Sony Inc., was the victim of an unprecedented cybersecurity attack launched by North Korean hackers. The attack was a result of the upcoming premiere of Sony;s film The Interview, a comedy based on a fictional attempted assassination of North Korean dictator Kim Jong-un. The group responsible subsequently threatened an attack on theaters choosing to show the film. Sony Pictures CEO Michael Lynton must decide whether or not to stop the movie;s release, while also protecting Sony's public image, maintaining distributor relations, minimizing revenue loss, and safeguarding employees data from further risk.
Originally published in Alexander, M., Chase, A., Chase, K., & O'Rourke, J. S. (2015). Sony Pictures Entertainment, Inc.: A cybersecurity attack from North Korea (B). 15-05 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sony Pictures Entertainment, Inc; Motion picture industry -- Security measures; Motion picture industry -- Public relations; Hacking; Crisis management